Comparative Analysis of Halal Tourism Management in Indonesia and China: Implementation, Challenges, and Opportunities - Adinugraha, Hendri Hermawan; Marier, Syauqie Muhammad; Al-Kasyaf, Muhammad Zheeva (RaSAIL Media Group, Semarang, Indonesia, 2025)
This study explores the implementation of halal management principles in the tourism industry in Indonesia and China as representatives of Muslim majority and minority countries. The main goal is to compare the effectiveness of regulations and infrastructure readiness and identify challenges and opportunities in developing halal tourism destinations. The study uses a qualitative, literature-based approach, analyzing regulatory documents, industry reports, and academic publications. The results of the analysis show that Indonesia adopts a regulation-based model with the support of national halal certification and halal industrial zones. At the same time, China prioritizes a market-based approach in areas with significant Muslim populations. Both countries face obstacles without global halal standards and limited provision of halal services in major destinations. This study highlights the importance of cross-sector collaboration, digital innovation, and policy harmonization to strengthen the competitiveness of global halal destinations. The contribution of this research lies in providing a comparative analysis that enriches the halal management literature and offers practical strategies for developing sustainable halal tourism.